Planning a High Capacity Longwall Project in SCCL Vis-à-Vis Challenges Encountered – A Saga of the Adriyala Longwall Project - Bhaskara Rao, B.; Veera Reddy, B. (Journal of Mines, Metals and Fuels, 2022)
No Abstract.